A motivação das decisões cíveis como condição de possibilidade para resposta correta / adequada - Motta, Cristina Reindolff da (Universidade do Vale do Rio dos Sinos, 2010)
The grounding constitutional right turns out to be an effective way to reach a correct/adequate answer to a decision and by also being the condition that enables the decision validation. It is through Hermeneutics together with the analysis of the substantial case that a correct/adequate decision to it can be reached. The interpretation of the norm is not up to the user being this the reason why the decisions ofthe substantial cases prescind from the Hermeneutics reading in order to have the correct understanding and enforcement of the law since the correct answer will only take place at the substantial case. The right decision at the substantial case must be based on law as integrity aside the discretion of the taker, who would be able to decide according tohis subjectivity by using the creative power given by the related discretion power. This is the crucial point of the foundational problem and its reasons why it turned into the citizen ́s fundamental right at the scope of welfare State and also as the fundamental duty of the judge/court. Hence, democracy will be inherently linked to the decision taking control. foundation does not mean any foundation since it cannot be given any meaning at a certain text.. The decision originated at philosophical hermeneutics reveals its entirely anti discretional side leading the correctanswer to the substantial case. The decision must show the criteria used so that it highlights its correction and also provide the direction for the future decisions. The lack of foundation promotes the absence of decisional criteria inasmuch as it hinders an external controlof the decisions. Thus the foundation as a means of the citizen ́s assurance, which is also restricting of the judger is essential garantee.
Keywords: Fundamentação; Decisão correta; Hermenêutica; Direito fundamental; Foundation; Fundamental right; Hermeneutics; Correct decision; ACCNPQ::Ciências Sociais Aplicadas::Direito